Modelling The Aids Epidemic In Malaysia - Ong, Hong Choon (2005)
There are generally three methods of modelling the acquired immuno deficiency syndrome (AIDS) epidemic. At one extreme is the attempt to fit a function of calendar time such as a polynomial or other mathematically convenient curves to the AIDS incidence curve while the other extreme attempts to model the full dynamics of the transmission of the epidemic in the population providing much insight into the qualitative evolution of the epidemic and idenifying the key variables that determine the future number of cases.